ASSESMENT BEBAN KERJA TERHADAP TINGKAT STRES PADA PEKERJA FABRIKASI, BEKISTING DAN PENGECORAN DI PT X - Rizky Endah Wijayanti; Hanifa Maher Denny; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Stress is a response through both physically and mentally from somebody, to something that is perceived as annoying and resulted in his being threatened in the neighborhood. One factor that causes stress is the workload. The purpose of this study was to determine the relationship of the workload and stress levels in workers fabrication, formwork and casting in PT X. This type of research is explanatory research using cross sectional approach. Total population 35 people. The sample used in this study using total sampling, because 5 people are no longer working, then sample this study amounted to 30 people. Data analysis using univariate analysis using frequency distribution and bivariate analysis using Chi-square test. These results indicate that workers with heavy work loads more levels of stress in the category of normal and mild stress compared with workers in the category of moderate stress and severe stress, which amounted to 66.7%. Most workers who experience stress on a relatively mild level of stress category. Results of bivariate analysis showed there was no relationship between workload stress levels (ρ-value 0.712). The conclusion of this study is the workload is not associated with the level of stress in workers fabrication, formwork and casting in PT X. The company should provide a resting place for the workers, making shift work at the time of casting and conduct work overtime refreshing program for workers.